Hepatic progenitors for liver disease: current position - Alice Conigliaro (Dove Medical Press, 2010)
Alice Conigliaro1, David A Brenner2, Tatiana Kisseleva21University “La Sapienza”, Dipartimento di Biotecnologie Cellulari ed Ematologia Policlinico Umberto I, V Clinica Medica, Rome, Italy; 2Department of Medicine, University of California, San Diego, La Jolla, CA, USAAbstract: Liver regeneration restores the original functionality of hepatocytes and cholangiocytes in response to injury. It is regulated on several levels, with different cellular populations contributing to this process, eg, hepatocytes, liver precursor cells, intrahepatic stem cells. In response to injury, mature hepatocytes have the capability to proliferate and give rise to new hepatocytes and cholangiocytes. Meanwhile, liver precursor cells (oval cells) have become the most recognized bipotential precursor cells in the damaged liver. They rapidly proliferate, change their cellular composition, and differentiate into hepatocytes and cholangiocytes to compensate for the cellular loss and maintain liver homeostasis. There is a growing body of evidence that oval cells originate from the intrahepatic stem cell(s), which in turn give(s) rise to epithelial, including oval cells, and/or other hepatic cells of nonepithelial origin. Since there is a close relationship between the liver and hematopoiesis, bone marrow derived cells can also contribute to liver regeneration by the fusion of myeloid cells with damaged hepatocytes, or differentiation of mesenchymal stem cells into hepatocyte-like cells. The current review discusses the contribution of different cells to liver regeneration and their characteristics.Keywords: hepatic progenitor, liver disease, liver precursor cells, oval cells, hepatocytes, intrahepatic stem cells, cholangiocytes